Odpowiedzi

Najlepsza Odpowiedź!
2009-11-12T21:54:26+01:00
2x-y=-5
x+2y=5 /^-2
2x-y=-5
-2x-4y=10
-5y=5
y=-1
x=3

3x+y=1
y=-2x
3x+y=1
2x+y=0 /^-1
3x+y=1
-2x-y=0
x=1
y=-2






2009-11-12T21:55:54+01:00
1) 2x-y=-5
x+2y=5 /-2y

2x-y=5
x=5-2y

2(5-2y)-y=-5
x=5-2y

10-4y-y=-5 /-10
x=5-2y

-5y=-15 /:-5
x=5-2y

y=3
x=5-2*3

x=-1
y=3

2) 3x+y=1
y=-2x

3x-2x=1
y=-2x

-5x=1 /:-5
y=-2x

x=-0,2
y=-2*-0,2

x=-0,2
y=0,4
2009-11-12T22:07:31+01:00
X=-2y+5
2*(-2y+5)-y=-5
-4y+10-y=-5
-5y=-15
y=3
x=-1

3x-2x=1
x=1
y=-2